2018
DOI: 10.1038/s41467-018-04687-7
|View full text |Cite
|
Sign up to set email alerts
|

Emissions mitigation opportunities for savanna countries from early dry season fire management

Abstract: Savanna fires produce significant emissions globally, but if managed effectively could provide an important mitigation opportunity, particularly in African least developed countries. Here we show global opportunities for emissions reductions through early dry season burning for 37 countries including: 29 countries in Africa (69.1 MtCO2-e yr−1), six countries in South America (13.3 MtCO2-e yr−1), and Australia and Papua New Guinea (6.9 MtCO2-e yr−1). Emissions reduction estimates are based on the successful app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
116
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(117 citation statements)
references
References 31 publications
0
116
0
1
Order By: Relevance
“…They found that, whilst annually variable, the savanna burning projects are meeting these goals. Due to these successes, Australia's Indigenous savanna burning program is considered a world leader, with interest from peoples in savanna regions globally to instigate similar programs [34]. Indigenous savanna burning projects aim to use cross-cultural science (Indigenous and western knowledge systems [35]) for best-practice adaptive management of fire, incorporating natural and cultural values.…”
Section: Introductionmentioning
confidence: 99%
“…They found that, whilst annually variable, the savanna burning projects are meeting these goals. Due to these successes, Australia's Indigenous savanna burning program is considered a world leader, with interest from peoples in savanna regions globally to instigate similar programs [34]. Indigenous savanna burning projects aim to use cross-cultural science (Indigenous and western knowledge systems [35]) for best-practice adaptive management of fire, incorporating natural and cultural values.…”
Section: Introductionmentioning
confidence: 99%
“…Such trade‐offs have received little attention (Abreu et al., ; Archibald, ; Richards et al., ). Given (a) the rapid up‐take of savanna burning (Figure ), (b) interest from some groups in adding biodiversity credits to fire projects (Fitzsimmons et al., ), and (c) the potential to apply savanna fire management for emissions control globally (Lipsett‐Moore et al., ), it is important that potential trade‐offs are considered, so that any negative impacts on biodiversity can be avoided.…”
Section: Potential For Bioperversity From Savanna Fire Managementmentioning
confidence: 99%
“…Tree plantings and avoided deforestation are two well‐known examples (e.g., Lindenmayer et al., ; Phelps, Friess, & Webb, ). Another potential example is fire management in tropical savannas, the most fire‐prone landscapes on Earth (Lipsett‐Moore, Wolff, & Game, ). Savanna fires emit substantial quantities of the greenhouse gases (GHG) methane and nitrous oxide, and “savanna burning,” an accountable activity under the Kyoto Protocol, has been identified as a major GHG abatement opportunity globally (Lipsett‐Moore et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, our findings here provide useful quantification of the degree to which different fire regimes can suppress aboveground carbon storage, and how this changes with spatial context. These trends are of global significance, at a time when many countries hosting the savanna biome are contemplating carbon sequestration initiatives (Bradshaw et al 2013, Russell-Smith et al 2013, Lipsett-Moore et al 2018.…”
Section: Implications For Managementmentioning
confidence: 99%